Proceedings of Second International Conference on Intelligent System ICIS 2023 - Tavares, João Manuel R. S.; Pal, Souvik; Gerogiannis, Vassilis C.; Hung, Bui Thanh (Algorithms for Intelligent Systems, 2024)
XIX, 593 p. 271 illus., 218 illus. in color.